1997
DOI: 10.1177/105256299702100404
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher as Container of Anxiety: Psychoanalysis and the Role of Teacher

Abstract: This article focuses on anxiety in teaching and learning. It argues that in essence the teacher's role is to contain anxiety for the sake of learning. The teacher's skill in setting up and maintaining a "containing space" is the keystone on which the various aspects of the art of good teaching rest. Within this space, learning can be experienced as the expansion of potential, not merely the mastery of content and predefined competencies. Despite the differences in aims, a strong "family resemblance" exists bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…After reading, writing, "rithmetic, the fourth "R" should be relationship (Bukowski, Laursen, & Hoza, 2010;Bukowski, Newcomb & Hartup, 1996). Indeed, it has been claimed that all learning occurs in within a relational context (French, 1997). The results have shown that there are close associations between the teacher-student relationships and the learning process, including aspects of motivation, interest and school well-being.…”
Section: Observation Sequence 01/28/2003mentioning
confidence: 72%
“…After reading, writing, "rithmetic, the fourth "R" should be relationship (Bukowski, Laursen, & Hoza, 2010;Bukowski, Newcomb & Hartup, 1996). Indeed, it has been claimed that all learning occurs in within a relational context (French, 1997). The results have shown that there are close associations between the teacher-student relationships and the learning process, including aspects of motivation, interest and school well-being.…”
Section: Observation Sequence 01/28/2003mentioning
confidence: 72%
“…For instance, Heron (1992) refers to the emotional competence required to acknowledge and live with feelings, both one's own and others'. The psychoanalytic literature on learning emphasises the need to contain anxiety and manage the dynamics of transference, both flattering and more hostile (French, 1997). Here, emotional resilience is a kind of expertise, not antithetical but complementary to the expertise of the intellect.…”
Section: Nuanced Understandings Of Expertisementioning
confidence: 99%
“…The greatest anxiety seemed to be mine! To shield myself from the anxiety of failing as the 'one who is supposed to know' (French, 1997), I had chosen a topic where I had a large repertoire of knowledge and illustrations upon which to draw. But in reality, my anxieties were not related to knowledge or expertise; they felt more closely connected with fears of personal rejection, including vague fears of being thought unattractive, in looks and/or personality.…”
Section: Expressing and Thrusting Into Spacementioning
confidence: 99%
“…Is it because feelings of violation are uncomfortable and will probably cause more problems in the sense that they demand more thought and more work, if they are to be taken more seriously? In any event, the case conference did not appear to help mobilise more mature mental capacity and enable Anne to overcome the unavoidable emotional imbalance that comes with being a teacher [43] [44]. Instead, it seems important for teachers avoid unbearable feelings.…”
Section: The Case Conferencementioning
confidence: 99%